Public-Private-Partnerships In Expanding German Education And Career Access For Marginalized Indian Youth - Singh, Amit Bachan (Digital Repository of Theses, 2025)
This study examines the role of Indo–German Public–Private Partnerships (PPPs) in expanding equitable access to vocational education and sustainable employment opportunities for marginalized Indian youth. Situated within the broader contexts of globalization, demographic transitions, and Germany’s acute skilled labor shortages, PPPs have emerged as strategic mechanisms connecting India’s large youth population with Germany’s dual vocational education and training (VET) model. Flagship initiatives such as IGVET and Make in India Mittelstand provide structured pathways through language instruction, apprenticeships, and cultural orientation. Yet, questions remain regarding their long-term effectiveness and inclusivity. Marginalized youth from Scheduled Castes, Scheduled Tribes, Other Backward Classes, and rural communities continue to face significant barriers, including financial constraints, systemic discrimination, limited language proficiency, and uneven institutional support. This study critically investigates whether PPPs genuinely foster social inclusion, enhance employability, and facilitate “brain circulation” rather than perpetuating one-way brain drain. Adopting a qualitative-dominant case study approach, the research draws on interviews, focus groups, and document analysis to examine program design, participant experiences, and both immediate and long-term outcomes. By foregrounding the lived experiences of participants, the study demonstrates how Indo–German PPPs operate as conditional catalysts of mobility and empowerment—effective when financial, linguistic, and psychosocial supports are integrated, but less so when such supports are fragmented or absent. The findings contribute to debates on international skill partnerships by offering equity-oriented recommendations for designing socially responsible, sustainable, and scalable PPP frameworks. These insights aim to inform policy and practice in both India and Germany, aligning future initiatives with broader global development and migration governance goals.